2016
DOI: 10.5144/0256-4947.2016.352
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of loop versus divided colostomy in the management of anorectal malformations

Abstract: BACKGROUNDColostomy is a common part of the management of high anorectal malformation (ARM) in the pediatric population.OBJECTIVETo evaluate whether the type of colostomy (loop vs divided) has an impact on outcome in patients with ARM.DESIGNA retrospective study.SETTINGKing Faisal Specialist Hospital and Research Center, a tertiary care center.PATIENTS AND METHODSAll patients who were managed with colostomy for ARM and had definitive repair during the period of January 2000 to December 2014. Outcomes relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…In 3140 patients 188 incisional hernias occurred 15 64 . None of the studies reported on the mode of diagnosis or the size of the defect.…”
Section: Resultsmentioning
confidence: 99%
“…In 3140 patients 188 incisional hernias occurred 15 64 . None of the studies reported on the mode of diagnosis or the size of the defect.…”
Section: Resultsmentioning
confidence: 99%
“…A stoma in a mobile portion of the colon is more likely to prolapse than one in a fixed portion of the colon. 9 Oda et al found 2.8% patients had prolapse after divided colostomy. 4 Six(5.17%) patients in the present study developed prolapse of colostomy, among which all developed on distal stoma site.…”
Section: Discussionmentioning
confidence: 96%
“…Almosallam et al conducted a retrospective study to evaluate whether the type of colostomy has an impact on outcome in patients with ARM where they found 2.04% developed retraction of colostomy. 9 Oda et al compared clinical outcome of loop and divided colostomies performed as part of the surgical management of ARM where they found 4.2% developed retraction of colostomy. 4 Divided colostomy has a low risk of prolapse or retraction.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of prolapses was reported previously to be higher when a long period between formation and closure of loop colostomies [5]. However, this seems not always be related to the type of stoma since Almossalam et al published a series of 55 LCs and 49 DCs and did not find any difference between complications in the 2 groups regardless of the duration of stoma [4]. Our data have similarly demonstrated no difference in prolapse rates in those who had stoma closure within or after 6 months.…”
Section: Discussionmentioning
confidence: 97%
“…Colostomy is performed in staged surgery for ARM to relieve the intestinal obstruction and allow bowel decompression prior to definitive reconstruction. However, the ideal type of colostomy has been debated by pediatric surgeons [3][4][5][6][7][8]. A divided colostomy (DC) created at the junction of the descending and sigmoid colon has been recommended [2].…”
Section: Discussionmentioning
confidence: 99%